Development of a framework for the reduction of manufacturing defects in a composite material process - Muhammad Iqbal Muhammad Hussain (School of Manufacturing Engineering, Universiti Malaysia Perlis, 2008)
A study that integrates the use of 'statistical design of experiments'(SDE), 'failure mode and effect analysis'(FMEA), several side experiments, control charts, and certain process controls is carried out. The study combines time-tested industrial problem-solving and process-improvement methods in a way that is both regimented as well as flexible, in line with the numerous uncertainties that inevitably present themselves in any livemanufacturing environment.